The Prevalence and Severity of Dental Fluorosis among Secondary School Children in Ibadan, Nigeria. (2012)
Objectives: This study was conducted to determine the prevalence and severity of dental fluorosis among secondary school children in Ibadan, Nigeria. Materials and methods: A multi-stage sampling technique was employed to select the participants who consisted of children aged 12-14 years taken from eleven randomly selected secondary schools in the five local government areas of Ibadan Metropolis. The children were examined by the Principal Investigator after submitting parental administered questionnaires. The diagnosis of dental fluorosis was based on the TF index. Results: The mean age of the 1372 participants (825 males and 547 females) was 13.15 + 0.80 years. Dental fluorosis was diagnosed in 157 (11.4%) children (98 males and 59 females). There was no statistically significant difference between age or gender and the occurrence of fluorosis. Most of the cases were very mild with greater than 90% of the affected teeth having a TF score of <3. The most severely affected were the maxillary molars. Severe disfiguring cases of dental fluorosis were not common among the secondary school children examined. Conclusion: The prevalence of dental fluorosis was found to be low, with majority of the cases being very mild.